2018
DOI: 10.1007/s00484-018-1527-1
|View full text |Cite
|
Sign up to set email alerts
|

How do season, on-farm fasting interval and lairage period affect swine welfare, carcass and meat quality traits?

Abstract: This study was carried out in order to determine the effects of different combinations of on-farm fasting intervals (8, 12, 16, 20 h) and 1.5 h of transport plus lairage periods (1, 3, 6 h) at different seasons (summer/winter) on blood stress parameters (cortisol and lactate), stomach content and weight, skin lesion and meat quality in a total of 960 pigs from eight farms. Blood lactate levels were greater in the summer (P < 0.001) and stomach content was affected (P < 0.05) by season, on-farm fasting interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
1
6
1
11
Order By: Relevance
“…The literature reported different results on the seasonal effect of skin lesion and ham defects in pigs. The present results are in contrast with what observed by Dalla Costa et al [ 31 ] and Cobanovic [ 32 ], who observed increased skin lesions in winter, and Arduini et al [ 20 ], who reported increased muscle tears in the cold seasons (winter and autumn). The results of the present study agreed with what has been claimed by Bottaccini et al [ 17 ] and Goumon et al [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The literature reported different results on the seasonal effect of skin lesion and ham defects in pigs. The present results are in contrast with what observed by Dalla Costa et al [ 31 ] and Cobanovic [ 32 ], who observed increased skin lesions in winter, and Arduini et al [ 20 ], who reported increased muscle tears in the cold seasons (winter and autumn). The results of the present study agreed with what has been claimed by Bottaccini et al [ 17 ] and Goumon et al [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The blood samples were centrifuged at 3500× g for 15 min at 4 • C, and then serum was separated and stored at −20 • C for further analysis. Then fatteners were slaughtered according to the recommendations of the animal welfare literature [12].…”
Section: Sample Collectionmentioning
confidence: 99%
“…Dall Aaslyng and Barton-Gade (2001) concluded that there is no need of lairage if preslaughter handling is inducing only low stress or in populations without the halothane gene. Prolonged periods of lairage can decrease pig welfare (Dalla Costa et al, 2019b). Nevertheless, to allow pigs to rest after transport, the lairage should allow the animal to satisfy comfort around resting (Welfare Quality ® , 2009) and thermal comfort as well as by providing enough space for the animal to be able to move around freely and to move away in case of aggressive behaviours.…”
Section: Lairagementioning
confidence: 99%